Artesunate versus quinine in the treatment of severe falciparum malaria in African children (AQUAMAT): an open-label, randomised trial - Dondorp, Arjen M; Fanello, Caterina I; Hendriksen, Ilse C E; Gomes, Ermelinda; Seni, Amir; Chhaganlal, Kajal D; Bojang, Kalifa; Olaosebikan, Rasaq; Mwanga-Amumpaire, Juliet; Anunobi, Nkechinyere; et al (The Lancet, 2010)
Background: Severe malaria is a major cause of childhood death and often the main reason for paediatric hospital admission in sub-Saharan Africa. Quinine is still the established treatment of choice, although evidence from Asia suggests that artesunate is associated with a lower mortality. We compared parenteral treatment with either artesunate or quinine in African children with severe malaria. Methods: This open-label, randomised trial was undertaken in 11 centres in nine African countries. Children (<15 years) with severe falciparum malaria were randomly assigned to parenteral artesunate or parenteral quinine. Randomisation was in blocks of 20, with study numbers corresponding to treatment allocations kept inside opaque sealed paper envelopes. The trial was open label at each site, and none of the investigators or trialists, apart from for the trial statistician, had access to the summaries of treatment allocations. The primary outcome measure was in-hospital mortality, analysed by intention to treat. This trial is registered, number ISRCTN50258054. Findings: 5425 children were enrolled; 2712 were assigned to artesunate and 2713 to quinine. All patients were analysed for the primary outcome. 230 (8·5%) patients assigned to artesunate treatment died compared with 297 (10·9%) assigned to quinine treatment (odds ratio [OR] stratiﬁ ed for study site 0·75, 95% CI 0·63–0·90; relative reduction 22·5%, 95% CI 8·1–36·9; p=0·0022). Incidence of neurological sequelae did not diﬀ er signiﬁ cantly between groups, but the development of coma (65/1832 [3·5%] with artesunate vs 91/1768 [5·1%] with quinine; OR 0·69 95% CI 0·49–0·95; p=0·0231), convulsions (224/2712 [8·3%] vs 273/2713 [10·1%]; OR 0·80, 0·66–0·97; p=0·0199), and deterioration of the coma score (166/2712 [6·1%] vs 208/2713 [7·7%]; OR 0·78, 0·64–0·97; p=0·0245) were all signiﬁ cantly less frequent in artesunate recipients than in quinine recipients. Post-treatment hypoglycaemia was also less frequent in patients assigned to artesunate than in those assigned to quinine (48/2712 [1·8%] vs 75/2713 [2·8%]; OR 0·63, 0·43–0·91; p=0·0134). Artesunate was well tolerated, with no serious drug-related adverse eﬀects. Interpretation: Artesunate substantially reduces mortality in African children with severe malaria. These data, together with a meta-analysis of all trials comparing artesunate and quinine, strongly suggest that parenteral artesunate should replace quinine as the treatment of choice for severe falciparum malaria worldwide.
Keywords: Artesunate; Quinine; African children; Treatment; Malaria